Practicality of Gamification-Based VPDLS Media and Its Association with Elementary School Students’ Digital Numeracy Achievement - Hasbiyah Srianah Amir; Poopathy Dhanasekaran (LEOTECH: Journal of Learning Education and Technology, 2026)
The development of digital learning media is essential in improving elementary school students’ digital numeracy skills. This study aims to analyze the practicality of gamification-based VPDLS media and examine its association with elementary school students’ digital numeracy achievement. A descriptive quantitative approach with comparative analysis was employed. The research involved 343 elementary school students from eight schools. Data were collected using a digital numeracy essay test and a media practicality questionnaire based on the Technology Acceptance Model. Instrument validity and reliability were analyzed using SmartPLS, while descriptive statistics and ANOVA were conducted using SPSS. The results showed that the VPDLS media demonstrated high practicality, with students perceiving it as easy to use, practical, and comfortable for learning. Students’ digital numeracy scores also showed relatively high achievement, with significant differences among schools. The ANOVA results confirmed that both media practicality and digital numeracy achievement varied significantly across learning contexts. These findings indicate that gamification-based VPDLS media has the potential to support students’ engagement in digital numeracy learning, although the results should be interpreted cautiously because the study employed a descriptive quantitative design. In addition, the high level of practicality contributes to students’ acceptance and consistent use of digital learning media. The results are expected to support teachers and educational practitioners in designing effective and user-friendly digital learning media. This study provides empirical evidence regarding the practicality and potential contribution of gamification-based VPDLS media in supporting digital numeracy learning at the elementary school level.